ChemInform Abstract: Copper(I)‐Catalyzed [3 + 2] Cycloaddition/Ring‐Opening Rearrangement/[4 + 2] Cycloaddition/Aromatization Cascade: An Unprecedented Chemo‐ and Stereoselective Three Component Coupling of Sulfonyl Azide, Alkyne and N‐Arylidenepyridin‐2‐amine to Pyrido[1, 2‐a]pyrimidin‐4‐imine. Issue 23 (16th May 2013) - Namitharan, Kayambu; Pitchumani, Kasi
Abstract An efficient, simple and new protocol for the synthesis of N‐substituted pyrido[1, 2‐a]pyrimidin‐4‐imine derivatives [cf.